C-reactive protein levels could be a prognosis predictor of prostate cancer: A meta-analysis - Zhou, Kechong; Li, Chao; Chen, Tao; Zhang, Xuejun; Ma, Baoluo (Frontiers in Endocrinology, 2023)
Background The relationship between the C-reactive protein (CRP) and prognosis in prostate cancer (PCa) has been widely discussed over the past few years but remains controversial. Material and methods In our meta-analysis, we searched 16 reliable studies in the PubMed, Embase, and Cochrane Library databases. Otherwise, we have successfully registered on the INPLASY. We also performed random- and fixed-effects models to evaluate the hazard ratio (HR) and 95% confidence interval (CI), respectively. Result The result of our meta-analysis shows that elevated CRP levels were related to worse overall survival (OS) (HR = 1.752, 95% CI = 1.304–2.355, p = 0.000), cancer-specific survival (CSS) (HR =1.823, 95%CI = 1.19-2.793, P = 0.006), p = 0.026), and progression-free survival (PFS) (HR = 1.663, 95% CI = 1.064–2.6, p = 0.026) of PCa patients. There was significant heterogeneity, so we performed a subgroup analysis according to the staging of the disease and found the same result. Furthermore, the heterogeneity was also reduced, and no statistical significance. Conclusion Our study shows that the level of CRP could reflect the prognosis of prostate cancer patients. We find that PCa patients with high levels of CRP often have worse OS, CSS, and PFS, although the stages of the patients’ disease are different. More studies are needed to verify this idea.